Global education: experiencing Japanese health care and culture through UKM outbound mobility program. - , Norafidah Abdul Rashid, Mazlina Mohtar, Noor Raihan Khamal (Universiti Kebangsaan Malaysia, 2014)
Ever since Universiti Kebangsaan Malaysia (UKM) signed the memorandum of agreement with Niigata University (NU) in 2009, several undergraduate and postgraduate students from both universities has been visiting NU and UKM through the student exchange programs. This year, three Doctor Of Public Health (DRPH) postgraduate candidates were fortunate enough to be chosen to conduct field attachment in Niigata Prefecture from 23rd November 2013 until 13th November 2013, which was organized by the International Health Division, Graduate School of Medical and Dental Sciences, Niigata University School of Medicine. These three weeks program covers various program involving governmental departments, hospitals, nursing homes and health centers.